Salivary Physicochemical Characteristics in Relation to Oral Health Status Among Institutionalized Autistic Adolescents in Baghdad/Iraq - Al-Fatlawi, Ali F; Radhi, Nada Jafer MH. (Journal of Baghdad College of Dentistry, 2017)
Background: Autism spectrum disorder (ASD) is characterized by impairments in social interaction and communication, restricted patterns of behavior, and unusual sensory sensitivities. Saliva may provide an easily accessible sample for analysis. Some salivary constituents levels altered in adolescents with ASD including antioxidants . This study aimed to investigate salivary physicochemical characteristic in relation to oral health status among adolescent with ASD. Materials and methods: Two groups were included in this study: forty institutionalized autistic adolescents and forty apparently healthy school adolescents with age range (12-15 years old, only males) selected randomly from Baghdad. Each group subdivided into two groups according to the severity of dental caries: caries free group (20 child, DMFT=0) and high caries group (20 child, DMFTâ‰¥6). Decayed, missing and filled surfaces (DMFS), plaque (PlI), Gingival (GI) and calculus (CI) indices were used to measure oral health status for both groups. Copper (Cu), zinc (Zn) and thiocyanate (SCN) in saliva measured by atomic absorption spectrophotometer. Salivary alpha amylase (sAA) and glutathione (GSH) assessed by enzyme-linked immunosorbent assay (ELISA). Salivary pH and flow rate were measured directly. The data of current study was analyzed using SPSS version 21. Results: A higher value of salivary pH, flow rate, sAA, SCN, Cu and Zn were found among study group than control group with significant difference, also higher in caries free subgroup than high caries subgroup. While GSH was higher in control group than study group. Moderate negative correlations between sAA, Cu, Zn and PlI, CI, GI with highly significant and salivary pH correlate moderately with PlI and CI with highly significant. Conclusion: There is alteration in salivary constituents levels which related to oral health status in adolescents with ASD and can act as adjunctive diagnostic aid for diagnosing autism.